Language change in a contact situation - Šabec, Nada (Slovenski jezik, 1999)
The article discusses the development of Slovene in the context of immigration to North America. The emphasis is on various changes observed on Different linguistic levels (morphology and ayntax in particular) which were brought about primarily through contact with the pragmatically dominant English.
Keywords: linguistics; lingvistika; oblikoslovje; priseljenci; Severna Amerika; Slovene; slovenski izseljenci; slovenščina; United States of America; ZDA